Antepartum Contraceptive Counseling in Women with Preterm Birth - Toscano, Marika; Li, Dongmei; Dye, Timothy; Olson-Chen, Courtney (American Journal of Perinatology, 2019)
Objective To compare rates of antepartum contraceptive counseling among women with preterm birth (PTB) and term birth.Study Design This is a retrospective cohort study of patients with completed delivery records in New York from January 1, 2004, to December 31, 2014. Exposure was determined based on the timing of delivery. Exposed women delivered at <37 weeks, and nonexposed women delivered at ≥37 weeks. Primary outcome was patient response to questions regarding receipt of prenatal contraceptive counseling (PCC) by a health care provider. Secondary outcome was receipt of interpregnancy interval counseling. Chi-square tests and multivariate logistic regression were used for analysis.Results Of 724,723 delivery records, PTB rate was 7.9%. Women with PTB < 37 weeks were significantly less likely to receive PCC (odds ratio [OR]: 0.9; 95% confidence interval [CI]: 0.89–0.93) or interpregnancy interval counseling (OR: 0.95; 95% CI: 0.94–0.97). The primary outcome remained significant after adjusting for confounders (adjusted OR: 0.91; 95% CI: 0.89–0.93). PTB < 34 weeks was associated with even lower odds of receiving contraceptive counseling (OR: 0.79; 95% CI: 0.76–0.83).Conclusion Postpartum contraception is an important tool for the prevention of recurrent PTB. Antepartum contraception counseling increases postpartum contraceptive uptake. Women with PTB have less exposure to antepartum contraceptive counseling. Lack of adequate counseling and decreased uptake of postpartum contraception may impact future pregnancy outcomes.
Keywords: preterm birth; antepartum contraceptive counseling; interpregnancy interval